Educación y Equidad de Género: Gaji Impacto en la Brecha: Education and Gender Equality: Impact on the Wage Gap - Jimenez Rodriguez, Luis alfredo; Torres, Jhon Edison Angarita; Suarez, Ramiro Gamboa (Management Science Research Journal, 2024)
Measure the degree of direct link between educational levels, gender and salary factor in the financial sector in Ocaña Colombia with the aforementioned labor market. The construct was based on the use of a descriptive quantitative approach and the data collection tool used was the interview. The target population was 150 employees of the financial sector of the municipality of Ocaña. The research development was based on obtaining necessary information so that with 3 specific objectives we could address the main objective. The subsidiary objectives allowed us to characterize each of the positions with the profiles and sexual orientation of the employees; on the other hand, they aimed to reveal the dimensions of human capital and the dynamics of the productivity of internal collaborators and, finally, to address a proposal focused on aspects and general administrative factors that help improve financial processes in the functions of the entities. That people still perceive fear of exposing their sexual orientation and gender identity in public, especially in the workplace. That there is still an inequality gap in access to the workplace, which, although it has been reduced and today there is a more inclusive role for women, it is still not equal to the access that men have to the work environment. The bias or limitation is recognized even today in the labor market that must now be separated as a labor practice. A series of strategies were formulated such as the creation of a policy framed in national and international criteria for the protection of human rights and labor rights focused on inclusion and diversity.